National Electronic Injury Surveillance System All Injury Program, 2003 ([Verlag nicht ermittelbar], 2005)
Beginning in July 2000, the National Center for Injury Prevention and Control (NCIPC), and Centers for Disease Control and Prevention (CDC), in collaboration with the United States Consumer Product Safety Commission (CPSC), expanded the National Electronic Injury Surveillance System (NEISS) to collect data on all types and causes of injuries treated in a representative sample of United States hospitals with emergency departments (ED). This system is called the NEISS All Injury Program (NEISS AIP). The NEISS AIP is designed to provide national incidence estimates of all types and external causes of nonfatal injuries and poisonings treated in United States hospital EDs. Data on injury-related visits are being obtained from a national sample of 66 out of 100 NEISS hospitals that were selected as a stratified probability sample of hospitals in the United States and its territories with a minimum of six beds and a 24-hour ED. The sample includes separate strata for very large, large, medium, and small hospitals, defined by the number of annual ED visits per hospital, and children's hospitals. The scope of reporting goes beyond routine reporting of injuries associated with consumer-related products in CPSC's jurisdiction to include all injuries and poisonings. The data can be used to (1) measure the magnitude and distribution of nonfatal injuries in the United States, (2) monitor unintentional and violence-related nonfatal injuries over time, (3) identify emerging injury problems, (4) identify specific cases for follow-up investigations of particular injury-related problems, and (5) set national priorities. A fundamental principle of this expansion effort is that preliminary surveillance data will be made available in a timely manner to a number of different federal agencies with unique and overlapping public health responsibilities and concerns. Also, annually, the final edited data are released as public use data files for use by other public health professionals and researchers. NEISS-AIP data on nonfatal injuries were collected from January through December each year except the year 2000 when data were collected from July through December (ICPSR 3582).NEISS AIP is providing data on approximately over 500,000 cases annually. Data obtained on each case include age, race/ethnicity, gender, principal diagnosis, primary body part affected, consumer products involved, disposition at ED discharge (i.e., hospitalized, transferred, treated and released, observation, died), locale where the injury occurred, work-relatedness, and a narrative description of the injury circumstances. Also, major categories of external cause of injury (e.g., motor vehicle, falls, cut/pierce, poisoning, fire/burn) and of intent of injury (e.g., unintentional, assault, intentional self-harm, legal intervention) are being coded for each case in a manner consistent with the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) coding rules and guidelines. NEISS has been managed and operated by the United States Consumer Product Safety Commission since 1972 and is used by the Commission for identifying and monitoring consumer product-related injuries and for assessing risk to all United States residents. These product-related injury data are used for educating consumers about hazardous products and for identifying injury-related cases used in detailed studies of specific products and associated hazard patterns. These studies set the stage for developing both voluntary and mandatory safety standards. Since the early 1980s, CPSC has assisted other federal agencies by using NEISS to collect injury- related data of special interest to them. In 1990, an interagency agreement was established between NCIPC and CPSC to (1) collect NEISS data on nonfatal firearm-related injuries for the CDC Firearm Injury Surveillance Study; (2) publish NEISS data on a variety of injury-related topics, such as in-line skating, firearms, BB and pellet guns, bicycles, boat propellers, personal water craft, and playground injuries; and (3) to address common concerns. CPSC also uses NEISS to collect data on work-related injuries for the National Institute of Occupational Safety and Health (NIOSH), CDC. In 1997, the interagency agreement was modified to conduct the three-month NEISS All Injury Pilot Study at 21 NEISS hospitals (see Quinlan KP, Thompson MP, Annest JL, et al. Expanding the National Electronic Injury Surveillance System to Monitor All Nonfatal Injuries Treated in US Hospital Emergency Departments. Annals Emerg. Med. 1999;34:637-643.) This study demonstrated the feasibility of expanding NEISS to collect data on all injuries. National estimates based on this study indicated product-related injuries that fall into CPSC's jurisdiction accounted for approximately 50 percent of injuries treated in U.S. hospital EDs. The study also indicated that NEISS is a cost-effective system for capturing data on all injuries treated in U.S. hospital EDs. The NEISS-AIP provides an excellent data source for monitoring national estimates of nonfatal injuries over time. Analysis and dissemination of these surveillance data through the ICPSR, and Internet publications will help support NCIPC's mission of reducing all types and causes of injuries in the United States, as well as assist other federal agencies with responsibilities for injury prevention and control.